2019
DOI: 10.3390/ijms20020377
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin Signaling in Cancer-Associated Inflammation

Abstract: The inflammatory and immune response elicited by the growth of cancer cells is a major element conditioning the tumor microenvironment, impinging on disease progression and patients’ prognosis. Semaphorin receptors are widely expressed in inflammatory cells, and their ligands are provided by tumor cells, featuring an intense signaling cross-talk at local and systemic levels. Moreover, diverse semaphorins control both cells of the innate and the antigen-specific immunity. Notably, semaphorin signals acting as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 62 publications
4
30
0
Order By: Relevance
“…SEMA3s also correlated with level of stromal cell infiltrates and immune cell infiltrates with various degrees based on the ESTIMATE algorithm. Those findings are consistent with the results of past observations that SEMA3s can function as pro-inflammatory and immune modulators [3,12,13,24], and they may be used as direct therapeutic targets or help predict the efficacy of immune checkpoint modulators in cancer patients. The association between SEMA3 gene expressions and tumor stemness score as well as with the drug sensitivity score indicated that SEMA3A, SEMA3C, and SEMA3F may mainly play tumor promotor roles during tumorigenesis as they are positively associated with tumor stemness and drug resistence scores.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…SEMA3s also correlated with level of stromal cell infiltrates and immune cell infiltrates with various degrees based on the ESTIMATE algorithm. Those findings are consistent with the results of past observations that SEMA3s can function as pro-inflammatory and immune modulators [3,12,13,24], and they may be used as direct therapeutic targets or help predict the efficacy of immune checkpoint modulators in cancer patients. The association between SEMA3 gene expressions and tumor stemness score as well as with the drug sensitivity score indicated that SEMA3A, SEMA3C, and SEMA3F may mainly play tumor promotor roles during tumorigenesis as they are positively associated with tumor stemness and drug resistence scores.…”
Section: Discussionsupporting
confidence: 92%
“…Instead, they were positively correlated with stem-cell-like features measured with DNA methylation (DNAss), suggesting they likely play a role in tumour initiating cells and relate with tumour resistance to drug treatment. SEMA3A has been extensively studied and it shows both pro-and anti-tumour effects [12,13,24]. Similar to previous reports, we found that SEMA3A was either up-or down-regulated in different cancer types, but we only found SEMA3A associated with poor prognosis in a number of cancer types (SARC, LUAD, HNSC, LGG, KIRC, and KIRP), where the expression of SEMA3A in tumours were all up-regulated.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Semaphorins were first identified as a family of genes encoding guidance molecules for the embryologic development of the nervous system [125,126]. The action mechanisms underlying semaphorins through their receptors from different cell types in different disease conditions had been summarized previously [127][128][129]. Cerani et al reported that neuron-derived Semaphorin3A is an early inducer of vascular permeability in diabetic retinopathy via neuropilin-1 [130].…”
Section: Neuron-derived Factors and Neovascularizationmentioning
confidence: 99%